2005
DOI: 10.1029/2004ja010800
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the tongue of ionization under northward interplanetary magnetic field conditions

Abstract: [1] The activities of the International Ionospheric Tomography Community open up new possibilities of simultaneously imaging the large-scale spatial structure of the ionosphere in different longitude sectors. In the study, tomography receiver chains in Scandinavia and Greenland were used to provide a wide view of the plasma density structure in the winter, magnetic postnoon sector under conditions of stable, positive interplanetary magnetic field B z component. The spatial distributions of the plasma are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…These signatures are very similar to the characteristics of the Tongue of Ionization (TOI) which has been reported as being frequently observed near the dayside discontinuity region (e.g. Middleton et al, 2005 and references therein). In order to be certain that our analysis is only restricted to wave phenomena, this interval has been excluded from our subsequent dission, and only the remaining periodic density fluctuations (TIDs) in the interval 08:00-12:00 UT in Fig.…”
Section: Esr Observations In the Polar Capsupporting
confidence: 61%
“…These signatures are very similar to the characteristics of the Tongue of Ionization (TOI) which has been reported as being frequently observed near the dayside discontinuity region (e.g. Middleton et al, 2005 and references therein). In order to be certain that our analysis is only restricted to wave phenomena, this interval has been excluded from our subsequent dission, and only the remaining periodic density fluctuations (TIDs) in the interval 08:00-12:00 UT in Fig.…”
Section: Esr Observations In the Polar Capsupporting
confidence: 61%
“…10), where the flow measurements were plentiful and revealed a sunward flow on lobe cells in the polar cap. This pattern was chosen because its general form was broadly similar to that inferred from DMSP cross-track observation shown in Middleton et al (2005), comprising sunward flow on the dayside near 12:00 MLT, and antisunward flow at lower latitudes on both the dawn and dusk sides. However, given the general variations between plasma convection patterns there were inevitably differences in detail.…”
Section: Ctip Model Outputmentioning
confidence: 99%
“…Three sample tomography reconstructions are also shown, showing the enhancement apparently becoming increasingly detached from the photoionisation with increasing MLT. The full set of reconstructions was presented and interpreted by Middleton et al (2005) with the enhanced densities being identified as cross-sections through a TOI (shown schematically by the purple curve in Fig. 9) drawn antisunward around the periphery of a polar cap closed to plasma inflow under the condition of northward IMF.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Closer inspection of the latter group showed that, in most cases, either IMF B z was close to zero or had become positive within two hours previous to observations and it was proposed that the patches under IMF B z positive had entered the polar cap under IMF B z negative (McEwen and Harris, 1996). Middleton et al (2005) observed a tongue-of-ionisation under conditions of IMF B z positive being swept around the periphery of the polar cap in the post-noon sector. Patch occurrence exhibits an UT dependence.…”
Section: Introductionmentioning
confidence: 99%